The buckling beam as actuator element for on-off hydraulic micro valves. Issue 1 (31st March 2021) - Scheidl, Rudolf; Scherrer, Matthias; Zagar, Philipp
The application of buckling beams for two types of micro valve actuation is studied in this paper by mathematical models. The first application type is the magnification of a short stroke actuator, such as piezo-electric stacks, to obtain the required stroke of the valve spool. The second application is the realisation of a spring with negative spring constant as an essential function element of a passive hydraulic binary counter which can control several binary coded valves by one flow control valve. The toggle mechanism as reference solution is mathematically analysed to elucidate the main properties. Four types of beams, only differing by their support structure, are analysed by analytical models employing a Rayleigh-Ritz approach. Models are evaluated to assess the performance properties of these beam types and to provide first order design rules.